If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (4x + -1) = -3x + -1(3 + -9x) Reorder the terms: 4x + (-1 + 4x) = -3x + -1(3 + -9x) Remove parenthesis around (-1 + 4x) 4x + -1 + 4x = -3x + -1(3 + -9x) Reorder the terms: -1 + 4x + 4x = -3x + -1(3 + -9x) Combine like terms: 4x + 4x = 8x -1 + 8x = -3x + -1(3 + -9x) -1 + 8x = -3x + (3 * -1 + -9x * -1) -1 + 8x = -3x + (-3 + 9x) Reorder the terms: -1 + 8x = -3 + -3x + 9x Combine like terms: -3x + 9x = 6x -1 + 8x = -3 + 6x Solving -1 + 8x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -1 + 8x + -6x = -3 + 6x + -6x Combine like terms: 8x + -6x = 2x -1 + 2x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 -1 + 2x = -3 + 0 -1 + 2x = -3 Add '1' to each side of the equation. -1 + 1 + 2x = -3 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = -3 + 1 2x = -3 + 1 Combine like terms: -3 + 1 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| -51-3x=-10x+82 | | 41+x-11=30 | | 3c^2-7c-21c+49= | | -11=4y+5 | | (4)=-2X+5 | | y^4z^2+8y^3z^2+16y^2z^2= | | -0.26n=169.39 | | (p+7)(4p-3)=0 | | -1+5=1-10 | | 0.04n=33.4 | | w^4-81=0 | | -11x-24=6-9x | | -1-6(2-9d)= | | y=x-v | | -3x^2+6x+24=0 | | 8p^3+64p^2+96p= | | 6x+2+x=1+5x-7 | | y=(3/4)1-2 | | 2(y-4)=5(y-7) | | y=(3/4)-1-2 | | -125-5x=139+7x | | -4(x-2)=-4x+8 | | 9-4(7-2x)= | | 4x^2-24x-220= | | 8=8r-(v+8) | | 3d+8(-d-5)= | | 6+6(2t+1)=3+12t | | 2x-72=97-11x | | 2z^2-4z-30= | | x^2-24x+72=0 | | 2.3y=20.7 | | 4x-4=7x-3 |